CRITICAL CURRENT DENSITIES OF SUPERCONDUCTING YBA2CU4O8 SYNTHESIZED BY THE CITRATE GEL PROCESS - Liu, R; Zheng, D; Janes, R; Campbell, A; Edwards, P (1990)
High-Tc superconducting YBa2Cu4O8 submicron powders with transition temperature around 80 K were successfully synthesized via citrate gel process at one atmosphere oxygen pressure. An intragrain critical current density of up to 1.3×107A/cm2 at 6 K and H=1 T has been measured by magnetisation method; this value is comparable to that found in sintered YBa2Cu3O7-δ. The integrain criticalcurrent density, as measured by an a.c. inductive technique, was 103 A/cm2 at 4.2 K; this is in excess of typical values for YBa2Cu3O7-δ. © 1990.